Investigating liquidity constraints as a channel of contagion: A regime switching approach - Rajan Sruthi; Santhakumar Shijin (Financial Innovation, 2020)
The present study investigates the timing and repercussion of the subprime crisis of 2008-09 in a regime-switching model. The interdependence and co-movement of financial markets in different countries has been enhanced due to the globalization of international trade, and investment trends can spread globally as a result of investors owning international portfolios. This study uses a regime-switching model to illustrate the timing of the crisis regime and calm regime for United States (US) stock index returns and the corresponding impact on Indian stock index returns. The Indian stocks investigated are classified into 'remote' and 'reachable' stocks, and different effects are found for these two types. It is found that shocks originating in the US can be transferred to the Indian reachable market as a result of foreign investors. There is, however, a less persistent impact on remote stocks. Accordingly, the study contributes to the literature on the material impacts of the crisis resulting from liquidity constraints and fear of contagion among investors.
Keywords: 650; Financial crisis; Financial contagion; Co-movement; Emerging market; Regime- switching